PENGELOLAAN ASET DAERAH ATAS TANAH MILIK PEMERINTAH DAERAH KABUPATEN PELALAWAN TAHUN 2015-2016 - Siti Romlah; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Regional assets are all property owned by the region either in the form of tangible goods or intangible goods. Regional assets as one important element in the framework of government administration and service to the community. Regional assets are an important resource for local governments because the assets or regional goods are the economic potentials owned by the regions. Economic potential means the financial and economic benefits that can be obtained in the future, which can support the role and function of local government as a provider of public services to the community. To maintain the regional assets in the form of land owned by the government of Pelalawan District, it is necessary to conduct certification as a proper step to arrange the regional assets owned by the local government of the pelalawan district. Certification is useful so as not taken and snatched by society hence required good management and certification of area asset of land owned by local government of Pelalawan Regency.The purpose of this research is to know the management of local asset of land owned by local government of Pelalawan Regency Year 2015-2016 and to know the obstacle in management of area asset of land owned by local government of Pelalawan Regency Year 2015-2016.This research uses qualitative research. This research was conducted in Pelalawan Regency. Techniques used to collect data in this study are (1) Interview, (2) Documentation.The conclusion of this research is (1) Management of Regional Assets on Land Owned by Local Government of Pelalawan Regency Year 2015-2016 done with 3 (three) management that is: First, Planning Needs Asset Area. Second, Record and Calculate assets/goods that become annual requirement of SKPD. Third, Registration of Plans of Needs and Maintenance of Regional Assets. (2) Obstacles in the Management of Regional Assets on Land Owned by Local Government of Pelalawan Regency. First, the lack of Human Resources (HR). Secondly, the Administration or Inventory which is still lacking by the Field of Assets of the Pelalawan District.Key words : Management, regional assets